Neutralizing monoclonal antibodies to human rotavirus and indications of antigenic drift among strains from neonates. - Coulson, B S (1985)
Cells producing neutralizing monoclonal antibodies to a serotype 3 human neonatal rotavirus strain RV-3 were derived by fusion of hyperimmunized mouse spleen cells with mouse myeloma cells. As ascites fluid, three rotavirus-neutralizing monoclonal antibodies were characterized by hemagglutination inhibition and reacted with 17 cultivable mammalian rotaviruses representing five virus serotypes, by fluorescent focus neutralization and enzyme immunoassay. Two antibodies, Mab RV-3:1 and Mab RV-3:2, reacted with the seven serotype 3 rotaviruses only. Mab RV-3:1 was shown to bind to the outer capsid glycoprotein gp34 of rotavirus when variants of SA 11 rotavirus were used, and it therefore appears to react with the major neutralization epitope of serotype 3 rotaviruses. The antibody Mab RV-3:3 was specific for an epitope of RV-3 rotavirus not present on any other rotavirus of any serotype tested, including another neonatal isolate of identical RNA electropherotype isolated from the same ward of the same hospital as RV-3 3 months earlier. These two viruses were also distinguishable by fluorescent focus neutralization, using antiserum to RV-3 virus. Western blot analysis showed binding of Mab RV-3:3 to the trypsin cleavage product of the outer capsid protein p86 of RV-3. This suggests that antigenic drift may have occurred among neonatal rotaviruses in Melbourne. These monoclonal antibodies will be useful in serotyping assays of rotaviruses directly in stool samples, and in further analysis of antigenic variation within the serotype.